PopLDdecay: a fast and effective tool for linkage disequilibrium decay analysis based on variant call format files - Zhang, Chi; Dong, Shan-Shan; Xu, Jun-Yang; He, Wei-Ming; Yang, Tie-Lin (Bioinformatics, 2019)
Abstract Motivation Linkage disequilibrium (LD) decay is of great interest in population genetic studies. However, no tool is available now to do LD decay analysis from variant call format (VCF) files directly. In addition, generation of pair-wise LD measurements for whole genome SNPs usually resulting in large storage wasting files. Results We developed PopLDdecay, an open source software, for LD decay analysis from VCF files. It is fast and is able to handle large number of variants from sequencing data. It is also storage saving by avoiding exporting pair-wise results of LD measurements. Subgroup analyses are also supported. Availability and implementation PopLDdecay is freely available at https://github.com/BGI-shenzhen/PopLDdecay.